The fama-french five-factor model: evidence from the JSE - Cox, Shaun (My University, 2018)
The desire to explain the returns of shares listed on stock exchanges has long driven research into asset pricing models. The formation of the Capital Asset Pricing Model (CAPM) served as the starting point for almost all models derived to describe share returns. Further research into returns discovered that there were various risk factors that impacted share returns; these could be captured by market value (size) and the book-to-market ratio (value). In 1993, Eugene Fama and Kenneth French used these to expand on the CAPM. The Fama-French three-factor model created a framework to model returns and allowed for other researchers to explore asset pricing further. In 2015, Fama and French augmented their profitability and investment factors onto their threefactor model. The author of this study postulated that these additional factors may proxy for quality, a formally undefined characteristic of shares that is used in selecting investments. This study tested the effectiveness of the five-factor model and the additional factors in explaining returns on the Johannesburg Securities Exchange (JSE). The five-factor model was compared to the traditional size-value three-factor model as well as other three-factor models that incorporated the additional factors. Furthermore, the study looked at what premiums are present in the returns on the JSE and captured by the various models tested. The results show that the size-value and size-profitability three-factor models best describe time-series returns when comparing models. The five-factor model best explains the crosssection of returns and overall, the results identify a strong inverse size effect and value and market premiums. Interestingly, the strength of the original size-value three-factor model is reinforced. The additional factors of profitability and investment contribute to explaining the returns on the JSE. Furthermore, profitability could be seen as a contributing factor in a “quality premium”. In addition to being a risk factor, quality could also be used as a filter through which the traditional premiums like size or value can be unlocked.
A research report submitted to the School of Economic and Business Sciences, Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment (50%) of the requirements for the degree of Master of Commerce in Finance, October 2018
Keywords: Johannesburg Stock Exchange; Capital assets pricing model